Proton irradiation of CdTe thin film photovoltaics deposited on cerium-doped space glass - Stuart Irvine (Progress in Photovoltaics: Research and Applications, 2017)
Space photovoltaics is dominated by multi-junction (III-V) technology. However, emerging applications will require solar arrays with high specific power (kW/kg), flexibility in stowage and deployment, and a significantly lower cost than the current III-V technology offers. This research demonstrates direct deposition of thin film CdTe onto the radiation-hard cover glass that is normally laminated to any solar cell deployed in space. Four CdTe samples, with 9 defined contact device areas of 0.25 cm2, were irradiated with protons of 0.5-MeV energy and varying fluences. At the lowest fluence, 1 × 1012 cm−2, the relative efficiency of the solar cells was 95%. Increasing the proton fluence to 1 × 1013 cm−2 and then 1 × 1014 cm−2 decreased the solar cell efficiency to 82% and 4%, respectively. At the fluence of 1 × 1013 cm−2, carrier concentration was reduced by an order of magnitude. Solar Cell Capacitance Simulator (SCAPS) modelling obtained a good fit from a reduction in shallow acceptor concentration with no change in the deep trap defect concentration. The more highly irradiated devices resulted in a buried junction characteristic of the external quantum efficiency, indicating further deterioration of the acceptor doping. This is explained by compensation from interstitial H+ formed by the proton absorption. An anneal of the 1 × 1014 cm−2 fluence devices gave an efficiency increase from 4% to 73% of the pre-irradiated levels, indicating that the compensation was reversible. CdTe with its rapid recovery through annealing demonstrates a radiation hardness to protons that is far superior to conventional multi-junction III-V solar cells.